Vegetative and reproductive growth behaviour of Xanthostemon chrysanthus (F. Muell.) benth. – an ornamental tree in Malaysia - Ahmad Nazarudin M. R.,; Tsan, F.Y. (Penerbit Universiti Kebangsaan Malaysia, 2018)
A study was conducted to investigate the duration of growth stages and flowering behaviour of a landscape tree, Xanthostemon chrysanthus (F. Muell.) Benth. This species is known as golden penda and locally known as jambu kuning. It is widely planted for urban beautification due to its distinctive coloured flowers. Under local climate condition, this species flowers throughout the year. However, the flowering of this species has not been studied extensively. In the present study, the growth of selected trees aged approximately six years after planting was monitored for a year. The growth duration was determined using the extended Biologishe Bundesanstalt, Bundessortenamt and Chemical Industry (BBCH) scale. Percentages of flower and fruit and new leaf abundances were expressed as estimated percentage of each stage as compared to total surface area of the tree crown. The vegetative and reproductive stages of the species required 198 and 176 days, respectively. The flowering period took about 40 days from inflorescence bud swelling to drying and senescence of stamens and petals. Unsynchronized flowering was observed among the trees. The occurrence of flowers was also influenced by the development of new leaves or fruits. The information on the duration of each growth stage and the flowering behaviour of the species may enhance a more detailed study related to flowering of urban trees in Malaysia.